Rekonstruksi Konsep Makki–Madani dalam Ulum al-Qur’an: Telaah Kritis atas Kriteria Klasik dan Relevansinya bagi Studi Tafsir Kontemporer - Dewi Maryam (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2025)
The conceptual and operational problems in the Makki–Madani classification, which has often been used as a periodization label but has yet to function optimally as a tool for tafs?r analysis. The main issue lies in the overlapping criteria of time, place, and audience, as well as weak weighing procedures when narrations differ or verses are of mixed nature. This research employs qualitative library research with content analysis and internal-external criticism of classical Ulum al-Qur’an literature and contemporary studies, then formulates a reconstruction model based on hierarchical criteria and cross-examination of linguistic-thematic indicators and social context. The findings show that rearranging the hierarchy (with time as the axis, and place and audience as reinforcing elements) along with a verification mechanism makes the determination of Makki–Madani more transparent, replicable, and more relevant for reading the communicative purpose of revelation. These findings also strengthen the integration of Ulum al-Qur’an with hermeneutic approaches in contemporary tafs?r. Practically, this framework helps researchers interpret surah coherence, map the development of da'wah themes, and avoid hasty contextual generalizations in recent studies. In conclusion, the reconstruction of Makki–Madani enhances the accountability of interpretation without severing ties with classical tradition.